Microbiology of lower respiratory tract infection in workers of garment industry of Kathmandu - Pant, S; Bhusal, KR; Manandhar, S (Journal of College of Medical Sciences-Nepal, 2015)
By mistake the wrong PDF was loaded for this article. The correct PDF was loaded on 19th September 2016. OBJECTIVES This study was designed with the objectives of describing the distribution pattern of microorganisms responsible for causing LRTI in the workers of garment industries. MATERIALS AND METHODS A total of 198 cases of suspected person of Lower Respiratory Tract infection (LRTI) LRTI were included in this study. This study was conducted between November 2009 to April 2010. Specimen for the study was expectorated sputum. Gram-stain, Ziehl-Neelsen stains and culture were performed. RESULTS On direct microscopic examination, 20.51% were Gram positive bacteria, 79.48% were Gram negative bacteria and 4% were smear positive AFB. On culture sensitivity examination, 22% percent showed growth of different bacteria in different culture media. The bacteria isolated from the samples included Klebsiella pneumoniae (15.38%), Proteus mirabilis (15.38%) and Citrobacterfruendii (15.38%). Gram Negative bacteria were found most susceptible to Ciprofloxacin (92.30%, 24/26) and Amikacin (92.30%, 24/26). Similarly, Gram Positive bacteria were found most susceptible to Ciprofloxacin (100%, 8/8) followed by Cloxacillin and Cephalexin (87.5%, 7/8). Smear positive AFB was significantly associated with not using the protective measures (mask) by workers and presence of symptoms (cough for more than two weeks, night sweat, hemoptysis and anorexia) (p=0.031). Culture positivity was significantly associated with symptoms like production of purulent sputum (p=0.045). CONCLUSION There was insignificant association between LRTI and risk factors present in working room of garment industries. Most of the isolates were sensitive to Ciprofloxacin and resistance to Ampicillin and Cephalexin. Journal of College of Medical Sciences-Nepal, 2014, Vol-10, No-3, 14-22